Odpowiedzi

Najlepsza Odpowiedź!
2010-01-02T12:52:03+01:00
5x+y= 9
2x+3y=1

y=9-5x
2x+3(9-5x)=1

y=9-5x
2x+27-15x=1

y=9-5x
-13x=-26

y=9-5x
x=2

y=9-5*2
x=2

y=-1
x=2

ODPOWIEDŹ: D. x= 2 y= -1
2 5 2
2010-01-02T12:54:54+01:00
5x+y=9 / *(-2)
2x+3y=1 /*5

-10x-2y= -18 / +
10x+15y=5 / +

13y=-13 /:13
y=-1


5x+y=9 / *-3
2x+3y=1

-15x-3y=-27 /+
2x+3y=1 /+

-13x=-26 /:(-13)
x=2

y=-1 x=2
odp.D
1 1 1
2010-01-02T12:55:14+01:00
5x+y= 9 | *(-3)
2x+3y= 1

-15x - 3y = -27
2x + 3y = 1

- 15x + 2x = -27 + 1
- 13 x = - 26 | : (-13)
x = 2

podstawiamy do drugiego równania :
2*2 + 3y = 1
3y = - 3 |: (-3)
y = -1

x = 2
y = - 1

czyli odp . D